Inducting first-year social work students : reflections on a discipline-specific approach to academic development - Khosa, Priscalia; Pillay, Roshini; Dube, Nkosiyazi (Social Work/Maatskaplike Werk, 2018)
First-year students at tertiary education institutions face multiple problems including under-preparedness, financial problems and adjustment to university. In response, some universities have introduced generic academic development programmes. In contrast, three educators from the Department of Social Work at the University of the Witwatersrand (UWits) engage in a reflective analysis of a discipline-specific academic development programme. Thematic content analysis was used to analyse transcripts of two focus group interviews with students and reflective reports written by two educators on strategies used to design the programme. Findings suggest that this programme meets the unique needs and professional identity development of Social Work students.